2012
DOI: 10.1103/physreva.86.052710
|View full text |Cite
|
Sign up to set email alerts
|

Interruption of the inner rotation initiated in isolated electron-driven molecular rotors

Abstract: An anthracene molecule substituted at the central ring by two aniline moieties able to rotate about the C-N bonds can be considered to be a prototype molecular rotor. Electron attachment into the lowest empty orbitals of this molecule leads to formation of long-lived (microseconds) negative ions. Elimination of a hydrogen molecule from these anions was observed in the gas phase by means of dissociative electron attachment spectroscopy. The experimental findings were interpreted using density functional theory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…(where M stands for a target parent molecule) closed-shell anions at incident electron energies around 1 eV [25][26][27][28][29][30]. Elimination of two hydrogen atoms from the molecular anion was observed in the DEA spectra of indole and related molecules [27], polyphenolic compounds [31], and other molecules able to form new more stable structures [32]. The present research provides some new insight into this interesting phenomenon.…”
Section: Dea To Many Molecules With Biological Activity Is Dominated mentioning
confidence: 67%
“…(where M stands for a target parent molecule) closed-shell anions at incident electron energies around 1 eV [25][26][27][28][29][30]. Elimination of two hydrogen atoms from the molecular anion was observed in the DEA spectra of indole and related molecules [27], polyphenolic compounds [31], and other molecules able to form new more stable structures [32]. The present research provides some new insight into this interesting phenomenon.…”
Section: Dea To Many Molecules With Biological Activity Is Dominated mentioning
confidence: 67%
“…Насколько известно авторам, выброс двух атомов водорода из ОМИ наблюдается (при низких энергиях электронов) лишь в тех случаях, когда молекула-мишень имеет определённую структуру: либо содержит несколько гидроксильных групп (полифенол) [11,12,33], либо существует возможность внутренних вращений одних частей молекулы по отношению к дру-гим, при которых происходит сближение атомов водо-рода [34]. В обоих случаях необходимо, чтобы в качестве нейтрального фрагмента образовалась молекула водо-рода: только при таком условии удаётся объяснить факт наблюдения анионов [M -2H] -при низких (вплоть до тепловых) энергиях электронов.…”
Section: ние фрагментов [M -2h]unclassified
“…The present Rapid Communication attracts attention to the possibility of using substantially different and less common experimental means to study internal rotations in molecular systems bearing an excess electron, i.e., molecular negative ions. In fact, our previous results [11,12] show that rotational motion in isolated molecules can be initiated by low-energy (0-15-eV) electron attachment via resonance mechanisms [13]. A dissociative electron attachment (DEA) study of dianilindoanthracene (DAA) [11] concluded that an incoming electron initiates rotational motion of (at least) one aniline substituent around a C-N bond of the long-lived (mass-spectrometrically detectable) molecular anion as schematically shown in Fig.…”
mentioning
confidence: 96%